Neuroprotective effect of erythropoietin in amyotrophic lateral sclerosis (ALS) model in vitro. Ultrastructural study - Nagańska, Ewa; Taraszewska, Anna; Matyja, Ewa; Grieb, Paweł; Rafałowska, Janina (Folia Neuropathologica, 2010)
Erythropoietin (EPO) is a chemokine hormone that is widely distributed throughout the body including nervous system. For last years its role as cytokine involved in many physiological processes out of the bone marrow has been suggested. Moreover, it plays a very important role in CNS as potential neuroprotective agent. There is much evidence that EPO protects neuronal cells in vitro and in vivo models of brain injury, independently of its erythropoietic action. The aim of this study was to determine the potential neuroprotective effects of erythropoietin on the glutamate-mediated injury of motor neurons (MNs) in vitro . The study was performed on organotypic cultures of the rat lumbar spinal cord subjected to glutamate uptake blocker, DL-threo-beta-hydroxyaspartate (THA) and pretreated with EPO. Ultrastructural study evidenced that the spinal cord cultures pretreated with EPO exhibited less severe neuronal injury. The cultures exposed to EPO + THA showed inhibition of early MNs degeneration, including various mode of degenerative changes caused by THA, whereas in the later period the typical postsynaptic necrotic changes of neuronal cells occurred. However, the ultrastructural characteristics of apoptotic MNs changes were not observed during the whole period of observation. The results of this study indicate that, in the model of chronic glutamate excitotoxicity, EPO exhibits the neuroprotective ability mainly through prevention of apoptotic neuronal changes.